Magnetic catalysis in hot and dense quark matter and quantum fluctuations - Fukushima, Kenji; Pawlowski, Jan M. (Arxiv, 2012)
We analyze chiral symmetry breaking in quark matter in an external magnetic field at zero and finite temperature and quark chemical potential. We first give a brief overview of analytic results within the mean-field approximation. There the critical temperature for chiral restoration is increased by the magnetic field effect. Then we investigate the effects of matter and quantum fluctuations on the Magnetic Catalysis. More specifically, we compute the critical coupling as a function of the magnetic field and the temperature for zero and finite quark chemical potential in the presence of quantum fluctuations. As soon as a non-zero temperature and/or density is turned on, long-range correlations are screened and the critical coupling is no longer vanishing. We extend our dynamical results beyond the leading-order bubble resummation which results in a non-local four-Fermi coupling. This includes in-medium meson effects on the more quantitative level.
Gesehen am 01.12.2017